On the Design of Tariff Policy : A Practical Guide to the Arguments For and Against Uniform Tariffs - Tarr, David G. (World Bank, Washington, DC, 2017)
This chapter examines the arguments for and against a uniform tariff structure. Arguments against uniformity are: terms of trade; ‘strategic,’ infant or restructuring industry considerations, revenue or balance of payments purposes, and tariffs as a negotiating tool at the WTO. Arguments in favor of uniformity are: political economy considerations; administrative convenience; and reduction of smuggling and corruption in customs. The author maintain that tariff uniformity is the best choice in practice. A uniform tariff conveys a number of advantages, the most important of which is that if the tariff is uniform, the gains to industry lobbying are much smaller (and may be negative), creating a kind of free-rider problem for the lobbying industry and dramatically reduces the incentive to lobby for protection. Then: (1) the level of protection is likely to be lower (the recent experience of Chile is a dramatic case in point); (2) there is a direct saving of resources from the reduced lobbying; (3) the reduction to the gains from lobbying for protection provides a vastly improved signal to valuable entrepreneurial talent which will thus be encouraged to create better and cheaper products; and (4) the reduction in resources devoted to lobbying will result in less corruption in government, which may have positive spillover effects into other dimensions of government activity.